Change patterns of mother-adolescent perceived parenting and the corresponding trajectories in their internalizing symptoms - WEN, Wen (Institutional Knowledge at Singapore Management University, 2023)
Adolescence is a challenging and sensitive developmental period in which mothers and adolescents may be vulnerable to internalizing symptoms. The current study aimed to understand how patterns of changes in mother-adolescent perceived parenting (i.e., mother-adolescent perceived parenting transition profiles) corresponded with trajectories of mothers' and adolescents' internalizing symptoms from early to late adolescence. The current study utilized a three-wave longitudinal data set of 604 adolescents (54% female, Mage = 12.92, SD = 0.92) and 595 mothers (Mage = 38.89, SD = 5.74) from Mexican-origin immigrant families and adopted mother-adolescent perceived parenting transition profiles from a previous study. Multiple group analyses showed that mother-adolescent dyads who agreed on high levels of positive parenting across the course of adolescence (i.e., Stable Both High) experienced the lowest levels of internalizing symptoms, whereas dyads that showed an inconsistent pattern of mixed profile typologies over time (i.e., Fluctuated) experienced high levels of internalizing symptoms. For mother-adolescent dyads that consistently showed a pattern in which mothers reported more positive parenting compared to their adolescent children (i.e., Stable Mother High), mothers experienced low levels of (and even a decrease in) internalizing symptoms, while adolescents experienced considerably high levels of internalizing symptoms over time. The results for the other two parenting transition profiles (i.e., Change to Both High and Change from Both High) are also discussed. The findings highlight the importance of developing separate adaptive interventions to reduce internalizing symptoms for mothers and children by considering their change patterns of perceived parenting during the course of adolescence.